Derivational Suffixes in the Reading Textbook of Sixth Grade Elementary School by Evan Moor - I Gede Arya Wiranata; IGB Wahyu Nugraha Putra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
This study focuses on derivational suffixes that are found in textbook